2017
DOI: 10.1016/j.ramd.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aerobic and resistance training of long duration on pro- and anti-inflammatory cytokines in rats

Abstract: a b s t r a c tObjective: To determine possible changes in serum concentrations of pro-and anti-inflammatory cytokines of eutrophic rats subjected to aerobic or resistance physical training. Methods: This study examined serum concentrations of TNF-␣, IFN-␥, IL-6, IL-10 and IL-1-␤ in rats that performed aerobic or resistance training for 16 weeks. Thirty-five Wistar rats (male adult) were divided into three groups: Control Group (CG), Aerobic Group (AG) and Resistance Group (RG). Rats were sacrificed 48 h after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…HIIT is a effective method of exercise to reduce body fat percentage which is an important factor in reducing the concentration of IL-6 [34]. The levels of IL-6 on the MIT group higher than HIIT on the study also supports the research results of Silva et al which found that IL-6 on a group of moderate aerobic exercise or heavier than the other exercise groups [35]. The high levels of IL-6 on the MIT group could possibly be mediated from the still high on magrofag adipose infiltration.…”
Section: Discussionsupporting
confidence: 80%
“…HIIT is a effective method of exercise to reduce body fat percentage which is an important factor in reducing the concentration of IL-6 [34]. The levels of IL-6 on the MIT group higher than HIIT on the study also supports the research results of Silva et al which found that IL-6 on a group of moderate aerobic exercise or heavier than the other exercise groups [35]. The high levels of IL-6 on the MIT group could possibly be mediated from the still high on magrofag adipose infiltration.…”
Section: Discussionsupporting
confidence: 80%
“…Long-term and short-term exercise activities by different intensity and duration have been reported to play an important role in the prevention and control of cardiovascular diseases (17). Consistent with the findings of the present study, 16 weeks of aerobic training resulted in improved TNF-α levels in rats (18) however, inconsistent with findings of the present study, 16 weeks of resistance training led to increase of TNF-α levels in rats (18); this contradiction in findings may be due to the type of training as well as the contractions in the aerobic and resistance training. Eight weeks of moderateintensity aerobic training resulted in a significant decrease in TNF-α levels as well as a decrease in activation of the IκBα/NF-κB pathway (19).…”
Section: Discussionsupporting
confidence: 68%
“…A previous meta-analysis reported that AE decreased C-reactive protein (CRP) and IL-6 in T2D patients suggesting that AE might be a therapeutic option to improve inflammation-induced insulin resistance in diabetic patients (Hayashino et al, 2014). Kohut et al (2006) demonstrated that AE significantly decreased circulating CRP, IL-6, IL-18, and TNF-α levels independent of β-adrenergic receptors and psychosocial factors (Kohut et al, 2006 (Perandini et al, 2015;Silva et al, 2017). You et al (2014) demonstrated that 20 weeks of AE reduced adipose tissue in the gluteal and abdominal areas and consequently decreased adiponectin production.…”
Section: Adipokines and Insulin Resistance: Possible Roles Of Aementioning
confidence: 99%
“…A previous meta-analysis reported that AE decreased C-reactive protein (CRP) and IL-6 in T2D patients suggesting that AE might be a therapeutic option to improve inflammation-induced insulin resistance in diabetic patients (Hayashino et al, 2014). Kohut et al (2006) demonstrated that AE significantly decreased circulating CRP, IL-6, IL-18, and TNF-α levels independent of β-adrenergic receptors and psychosocial factors (Kohut et al, 2006) Long-duration AE programs with weight loss appear to be more effective in the reduction of adipokine secretion by adipocytes than acute periods of training that are accompanied with low or no weight loss (Silva et al, 2017;You et al, 2014). However, AE can decrease inflammatory mediators without any decline in total fat mass (Koh & Park, 2017).…”
Section: Adipokines and Insulin Resistance: Possible Roles Of Aementioning
confidence: 99%